Bilateral Basal Ganglion Hemorrhage after Severe Olanzapine Intoxication - Kerstin Schweyer; Bastian Fatke; Kornelia Kreiser; Christian Rabe; Christian Seifert; Benno Ikenberg (Case Reports in Psychiatry)
Olanzapine is a second-generation antipsychotic drug which is generally considered safe with well therapeutic antipsychotic effects. We describe a patient suffering from bilateral intracerebral hemorrhage after severe olanzapine intoxication without underlying thrombocytopenia, arterial hypertension, or vascular malformation as cause of intracerebral hemorrhage. This raises the possibility of a direct side effect of high-dose olanzapine intake. So far, intracranial hemorrhage after olanzapine intoxication in such constellation has not been reported before. Given the high number of its prescription rates, our finding of intracranial hemorrhage after olanzapine intoxication is of high clinical relevance.